PENGARUH MEDIA SOSIAL INSTAGRAM TERHADAP PERILAKU PROKRASTINASI AKADEMIK SISWA PADA MATA PELAJARAN IPS - Vina Lutfiah; Binti Maunah (JIIPSI: Jurnal Ilmiah Ilmu Pengetahuan Sosial Indonesia, 2023)
Academic procrastination can occur among students due to addiction to social media, especially Instagram social media. So that it impact often delays assignments or homework (PR) on a subject, especially on social studies subjects and a lack of maximum results. Procrastination is the postponement of assignments carried out on types of formal assignments related to academic assignments, for example school assignments and course assignments. The aim of this study was to determine the influence of Instagram social media on students' academic procrastination behavior in social studies subjects at SMPN 6 Tulungagung. This research is a quantitative research with associative. The subjects in this study were 40 students in class VIII F–VIII K. The sampling technique used was purposive sampling. The data analysis method used is Simple Linear Regression with the help of SPSS for Windows 16.0. Based on the data analysis, the regression coefficient value obtained from the simple linear regression test results is 0.544, and the sig = 0.000 (0.000 <0.05) so that it can be said that there is a positive and significant influence between the two variables. Judging from the data value (R) = 0.679 and the R Square value is 0.461. So it can be concluded that there is a significant influence between the use of Instagram social media on student procrastination behavior in social studies subjects of 46.1% while 53.9% is influenced by other factors not examined. Keywords: Influence, Social Media Instagram, Academic Procrastination